PELAKSANAAN FUNGSI UPT PERPARKIRAN DALAM PENGELOLAAN RETRIBUSI PARKIR DI KOTA PEKANBARU TAHUN 2021-2022 - Siswanto, Yogi; ', Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The implementation of the parking upt function in Pekanbaru in managing parking is contained in Mayor Regulation (Perwako) Number 138 of 2020 concerning Parking Management. The source of regional revenue in Pekanbaru City that is more likely to be developed at this time is parking levy revenue, because based on information from the Head of the Pekanbaru City Regional Revenue Service (Dispenda) that levy revenue in Pekanbaru City still really needs to be improved. Revenue from collecting parking fees to achieve the results targeted by the city government can be realized well. The theoretical concept used is that a one-sided public legal action is an action whose legal consequences arise directly as the government carries out the action without waiting for a reaction from the affected parties; Double-sided public legal acts: This double-sided public legal act has legal consequences that only arise after there is an agreement between the government and the affected parties. The type of research used in this research is descriptive research using a qualitative approach. Research that analyzes and produces data in the form of speech, writing and behavior from the people being observed. Based on the results of research on the actions of the Pekanbaru City Transportation Department government regarding parking management, it can be seen that the Pekanbaru City Transportation Department has been appointed as the agency that will manage parking based on Perwako Pekanbaru No. 132 of 2020. Determined as a Technical Implementation Unit that implements the financial management pattern of the Regional Public Service Agency (BLUD) based on the Decree of the Mayor of Pekanbaru Number 647 of 2019 concerning the establishment of a Parking Technical Implementation Unit at the Pekanbaru City Transportation Service, in addition to complying with the provisions of article 43 of the Regulation Minister of Home Affairs Number 79 of 2018 concerning Regional Public Service Bodies requires Minimum Service Standards for Parking Technical Implementation Units that implement the Financial Management Pattern of Regional Public Service Bodies. Keywords: Function implementation, Pekanbaru parking upt, parking levy